Sensitivity to permethrin in a Dermacentor reticulatus population from eastern Poland in laboratory study - Buczek, Alicja (BioMed Central, 2014)
BACKGROUND: The action of chemical compounds on the Palaearctic tick D. reticulatus (Fabricius) (Acari: Amblyomminae) has been poorly investigated so far. Therefore, the effects of application of permethrin on engorged D. reticulatus females have been assessed, and the survival rate for the different developmental stages of the tick species in its non-parasitic phase of the life cycle was determined upon application of the pyrethroid. METHODS: Each engorged D. reticulatus female, egg batch, unfed larvae (50 specimens), or unfed nymphs (10 specimens) were sprayed with 20 μl of 0.015625%- 0.250% solutions of a Coopex WP preparation, which corresponded to 0.78125- 12.5 μg of permethrin, respectively. The effect of permethrin in the preoviposition and oviposition periods was assessed based on the length of the egg development period, number of females capable of laying eggs, number and weight of eggs laid by the females, and indicators of female reproductive rate. Delayed effects of the action of the various permethrin doses were determined by quantitative and qualitative analysis of the course of embryonic development and larval hatch. The effect of permethrin on survival of the different tick stages was assessed at a temperature of 25°C and 90% RH 48 hours after application of permethrin to one to three day-old D. reticulatus eggs, seven to ten-day-old unfed larvae and nymphs. RESULTS: The investigations demonstrated that at the doses applied permethrin decreased the reproductive rate of females, but only at the dose of 6.25 μg/1 specimen was the mean number of laid eggs drastically reduced, which may result in a decrease in tick abundance already in the first generation. The embryonic development of the eggs laid by the females treated with 6.25 and 12.5 μg of permethrin/1 specimen was highly disturbed. Irrespective of the permethrin dose applied, all eggs died within 48 hours after application. 100% of unfed D. reticulatus larvae and nymphs died within 48 hours after application of permethrin doses of 6.25 μg/50 specimens and 12.5 μg/10 specimens, respectively. CONCLUSIONS: Permethrin can be recommended for D. reticulatus control, particularly in the case of tick resistance to other chemical substances.